Troglitazone inhibits hepatic oval cell proliferation by inducing cell cycle arrest through Hippo/YAP pathway regulation. Issue 6 (June 2022) - He, Yifeng; Li, Haijian; He, Yunhe; Lu, Caijie; Zhu, Peiyi; Li, Mingyi; Duan, Juan; Fang, Zhixin
Abstract: Hepatic oval cells have strong proliferation and differentiation capabilities and are activated when chronic liver injury occurs or when liver function is severely impaired. Peroxisome proliferation-activated receptors (PPARs) are ligand-dependent, sequence-specific nuclear transcription factors. PPARγ is closely related to liver diseases (such as liver cancer, liver fibrosis and non-alcoholic fatty liver disease). As the main effector downstream of the Hippo signaling pathway, YAP can activate the hepatic progenitor cell program, and different expression or activity levels of YAP can determine different liver cell fates. We found that troglitazone (TRO), a classic PPARγ activator, can inhibit the growth of hepatic oval cells, and flow cytometry results showed that TRO inhibited the growth of WB-F344 cells by arresting the cells in the G0/1 phase. Western blot results also confirmed changes in G0/1 phase-related protein expression. Further experiments showed that PPARγ agonists induced hepatic oval cell proliferation inhibition and cell cycle G0/1 phase arrest through the Hippo/YAP pathway. Our experiment demonstrated, for the first time, the relationship between PPARγ and the Hippo/YAP pathway in liver oval cells and revealed that PPARγ acts as a negative regulator of liver regeneration by inhibiting the proliferation of oval cells.